Pre-existing humoral immunity and complement pathway contribute to immunogenicity of adeno-associated virus (AAV) vector in human blood - Smith, Corinne J.; Ross, Nikki; Kamal, Ali; Kim, Kevin Y.; Kropf, Elizabeth; Deschatelets, Pascal; Francois, Cedric; Quinn, William J.; Singh, Inderpal; Majowicz, Anna; Mingozzi, Federico; Kuranda, Klaudia (Frontiers in immunology, 2022)
AAV gene transfer is a promising treatment for many patients with life-threatening genetic diseases. However, host immune response to the vector poses a significant challenge for the durability and safety of AAV-mediated gene therapy. Here, we characterize the innate immune response to AAV in human whole blood. We identified neutrophils, monocyte-related dendritic cells, and monocytes as the most prevalent cell subsets able to internalize AAV particles, while conventional dendritic cells were the most activated in terms of the CD86 co-stimulatory molecule upregulation. Although low titers (≤1:10) of AAV neutralizing antibodies (NAb) in blood did not have profound effects on the innate immune response to AAV, higher NAb titers (≥1:100) significantly increased pro-inflammatory cytokine/chemokine secretion, vector uptake by antigen presenting cells (APCs) and complement activation. Interestingly, both full and empty viral particles were equally potent in inducing complement activation and cytokine secretion. By using a compstatin-based C3 and C3b inhibitor, APL-9, we demonstrated that complement pathway inhibition lowered CD86 levels on APCs, AAV uptake, and cytokine/chemokine secretion in response to AAV. Together these results suggest that the pre-existing humoral immunity to AAV may contribute to trigger adverse immune responses observed in AAV-based gene therapy, and that blockade of complement pathway may warrant further investigation as a potential strategy for decreasing immunogenicity of AAV-based therapeutics.